Effect of filler size and filler loading on wear of experimental flowable resin composites - Koichi Shinkai; Yoshihisa Taira; Shiro Suzuki; Satoki Kawashima; Masaya Suzuki (University of São Paulo, 2018)
Abstract The relationship between wear resistance and filler size or filler loading was clarified for the universal resin composite; however, their relationship in flowable resin composites has not been clarified. Objectives: The purpose of this study was to investigate the effect of filler size and filler loading on wear of experimental flowable resin composites by using a cyclic loading device. Material and Methods: Nine experimental flowable resin composites consisting of three different sizes (70, 200 and 400 nm) and loading (50, 55 and 60 wt%) of filler were prepared. Bowl-shaped cavities were prepared on a flat surface of ceramic blocks using a No. 149 regular cut diamond point. The cavities were treated with a silane coupling agent and an all-in-one adhesive and then filled with each experimental flowable resin composite. The restored surfaces were finished and polished with a 1500-grit silicon carbide paper. The specimens were subjected to an in vitro two-body wear test using a cyclic loading device. The localized worn surfaces were evaluated at 10,000, 20,000, 30,000, and 40,000 cycles using a computer-controlled three-dimensional measuring microscope (n=5). The volumetric wear loss of the materials was calculated automatically by the equipment. Data were statistically analyzed with two-way ANOVA and post hoc Tukey test. Results: Two-way ANOVA showed that the filler size significantly influenced wear volume (p<0.003), but the filler loading did not have a significant effect (p>0.05). A post hoc Tukey test detected significant differences in filler size between 70 nm and 400 nm, and 200 nm and 400 nm (p<0.007). Conclusion: The experimental flowable resin composite containing a mean filler size of 400 nm exhibited significantly lower wear resistance in two-body wear compared with those containing mean filler sizes of 200 nm or 70 nm.